1988
DOI: 10.1227/00006123-198811000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Postoperative Normalization of Growth Hormone Levels in Two Patients with Acromegaly Not Cured by Transsphenoidal Surgery

Abstract: Postoperative persistence of elevated growth hormone (GH) levels in patients with acromegaly usually suggests residual adenoma tissue secreting GH and is an indication for further treatment. In rare cases, spontaneous normalization of serum GH levels in patients with acromegaly has been reported to occur as a consequence of intratumoral hemorrhage (pituitary apoplexy). We report two patients in whom persisting acromegaly was documented 1 and 2 weeks, respectively, after transsphenoidal operation and who experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…30 Conservative management can also be chosen for stable patients after administration of corticosteroids, as on serial neuroimaging, tumour reduction or even resolution due to apoplexy or necrosis have been reported. 31,32 Improvements in visual field defects and visual acuity has been seen with conservative treatment 33 and have been reported to be similar to surgical treatment. 34 However, it is recommended that the patient be monitored closely with daily clinical and neurological examination, including cranial nerves and visual fields as well as assessment of visual acuity.…”
Section: Discussionmentioning
confidence: 89%
“…30 Conservative management can also be chosen for stable patients after administration of corticosteroids, as on serial neuroimaging, tumour reduction or even resolution due to apoplexy or necrosis have been reported. 31,32 Improvements in visual field defects and visual acuity has been seen with conservative treatment 33 and have been reported to be similar to surgical treatment. 34 However, it is recommended that the patient be monitored closely with daily clinical and neurological examination, including cranial nerves and visual fields as well as assessment of visual acuity.…”
Section: Discussionmentioning
confidence: 89%
“…On the contrary, for those who have no symptoms of optic chiasma compression or consciousness impairment, hormonal replacement therapy should be the fi rst choice treatment. Most of these tumors may shrink spontaneously overtime [18,19] . Three patients with pituitary apoplexy, who had been admitted to our center simultaneously, were treated by hormonal replacement therapy, as their symptoms were mild.…”
Section: Surgical Treatment For Pituitary Apoplexymentioning
confidence: 99%
“…This was subsequent to the 34 cases initially reported in the 1950s. 2 Their report revealed that pregnancies occurred in varied clinical settings of acromegaly, ranging from undiagnosed, untreated acromegaly 2,3 to patients treated with bromocriptine 4 , octreotide 5 and transsphenoidal surgery without 6,7 or with 8 fertility treatment. The majority of reported cases were treated with bromocriptine 4 only or in combination with radiation 9 or surgery.…”
Section: Introductionmentioning
confidence: 99%